Comparing flipped classroom and conventional live demonstration for teaching orthodontic wire-bending skill - Lau, May Nak (Public Library of Science, 2021)
Flipped classroom may overcome weaknesses of live demonstration in teaching orthodontic wire-bending. This study aims to compare the effectiveness between flipped classroom and live demonstration in transferring skills for fabricating Adams clasp. Forty third-year undergraduate dental students were assigned to two groups. The students in group LD (n = 20) attended a live demonstration while students in group FC (n = 20) attended a flipped classroom. Both groups were taught on skills to fabricate Adams clasp in a standardised way. Each student from both groups were asked to submit an Adams clasp for a blinded quality assessment by two trained and calibrated assessors using a 18-item rubric, followed by validated students' satisfaction questionnaires to evaluate their perceived satisfaction on the teaching method received. A crossover study was then conducted three weeks later where LD attended a flipped classroom while FC attended a live demonstration. Students' satisfaction questionnaires were again collected from each student for blinded analysis. Mean scores for the quality of Adams clasp were 9.775 and 9.125 for LD and FC, respectively. No significant difference was detected between the two groups. Statistically significant association was found for one statement on the questionnaire, ``I found the classroom arrangements conducive for the wire-bending activity'' (p = 0.010). No significant differences were found between the two groups for other statements (p > 0.05). In conclusion, within the limitations of the study, flipped classroom is equally effective as conventional live demonstration in transferring orthodontic wire-bending skills for fabrication of Adams clasp. However, students perceived the classroom arrangements during the flipped classroom significantly more conducive for teaching orthodontic wire-bending.